2014
DOI: 10.5539/jas.v6n9p198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oil Content and Fatty Acid Compositions of Flax (Linum usitatissimum L.) Varieties of India

Abstract: Flax (Linum usitatissimum L.) is the third largest natural fiber crop and one of the five major oil crops in the world. An experiment was conducted to evaluate the oil content and fatty acid compositions of flax varieties grown in Chhattisgarh state of India. The oil content ranged from 33.97% to 42.27% in the experimental material. The highest oil content was recorded for variety Deepika (42.27%) followed by Indira Alsi-32 (42.12%), Sharda (41.12%) and Kartika (41.11%). Two saturated (Palmatic and stearic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
11
23
0
1
Order By: Relevance
“…You et al (2014) found that both linoleic and linolenic acids have a common biosynthesis pathway, so one can increase at the cost of the other. Similar findings were also reported by Bayrak et al (2010) and Pali & Mehta (2014). The results obtained in the present study indicate that high oil content will result in high oleic acid, tending to increase linolenic acid and reduce oleic and linoleic acids.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…You et al (2014) found that both linoleic and linolenic acids have a common biosynthesis pathway, so one can increase at the cost of the other. Similar findings were also reported by Bayrak et al (2010) and Pali & Mehta (2014). The results obtained in the present study indicate that high oil content will result in high oleic acid, tending to increase linolenic acid and reduce oleic and linoleic acids.…”
Section: Resultssupporting
confidence: 80%
“…According to Diederichsen & Fu (2008), the increase in seed weight affects oil concentration and amount per seed. The strong positive correlation observed between oil content and test weight is also in alignment with the findings of Rahimi et al (2011), andPali &Mehta (2014). The positive correlation of linolenic acid with days to maturity, plant weight, tillers per plant, secondary branches per plant, capsules per plant, and seed yield indicated that selection based on these traits would be useful in the development of varieties rich in linolenic acid.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations